Irrigation Investment and Market Analysis Study - Wanyama, Joshua (Agribusiness Initiative Trust Uganda Ltd, 2018)
The agricultural sector in Uganda faces increasing incidence of prolonged drought and unreliable rainfall attributed to climate change resulting into decline in agricultural productivity and household incomes. However, Uganda has an irrigation potential estimated at about 3,030,000 ha with only less than 1% currently exploited by less than 1% of agricultural households. In addition, access to water for livestock at present is estimated at 48.8%. Lessons learned from the past 8 years indicate increasing importance of irrigation as one of the key factors for increasing productivity, incomes and competitiveness of agribusinesses in both domestic and international markets. Evidence shows that irrigation can increase yields of coffee, vegetables and fruits by 2 to 4 fold stabilize and increase production and enhance product quality. It is against this background that a study was carried out to identify priority areas for enhancing private-sector investment and adoption of irrigation technologies by SMEs and small scale farmers.